2014
DOI: 10.1016/j.envint.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Perceived environmental and health risks of nuclear energy in Taiwan after Fukushima nuclear disaster

Abstract: After the nuclear disaster in Fukushima in Japan in 2011, a nation-wide survey using a standardized self-administered questionnaire was conducted in Taiwan, with a sample size of 2,742 individuals including the residents who live within and beyond 30 km from a nuclear power plant (NPP), to evaluate the participants' perceived nuclear risk in comparison with their perceived risks from selected environmental hazards and human behaviors. The three leading concerns of nuclear energy were "nuclear accidents (82.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Also, negative outcomes of a human-made hazard are evaluated more negatively than a natural hazard with the same outcomes (Siegrist and Sütterlin 2014). Concerns about chemical fires are likely to be focused on the unknown health risk associated with the composition of the smoke and the presence of chemicals with the predicate toxic, hazardous or carcinogenic (see for example: Ho et al (Ho et al 2014)). Furthermore, if a person has no perspective for action and no possibilities to control the outcomes, he will more likely be afraid.…”
Section: Discussionmentioning
confidence: 99%
“…Also, negative outcomes of a human-made hazard are evaluated more negatively than a natural hazard with the same outcomes (Siegrist and Sütterlin 2014). Concerns about chemical fires are likely to be focused on the unknown health risk associated with the composition of the smoke and the presence of chemicals with the predicate toxic, hazardous or carcinogenic (see for example: Ho et al (Ho et al 2014)). Furthermore, if a person has no perspective for action and no possibilities to control the outcomes, he will more likely be afraid.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were conducted to investigate public risk perception after the Fukushima accident in Japan and its neighboring countries such as Taiwan, South Korea and China [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…while the general public in Taiwan and South Korea were concerned more about the safety of nuclear operation, potential large-scaled harm to the public, and other negative social consequences associated with nuclear accidents [3][4][5][6]. Most importantly, these studies showed a reverse association between risk perception and the public acceptance for nuclear facilities.…”
mentioning
confidence: 99%
See 2 more Smart Citations